Neurodevelopmental pathways in bipolar disorder. (May 2020) - Kloiber, Stefan; Rosenblat, Joshua D.; Husain, Muhammad I.; Ortiz, Abigail; Berk, Michael; Quevedo, Joao; Vieta, Eduard; Maes, Michael; Birmaher, Boris; Soares, Jair C.; Carvalho, Andre F.
Highlights: Neurodevelopmental pathways are implicated in the pathophysiology of several mental disorders. Schizophrenia and bipolar disorder (BD) share several genetic and pathophysiological mechanisms. A comprehensive review of evidence linking BD to neurodevelopmental abnormalities is provided. Overall schizophrenia has been more consistently associated with neurodevelopmental aberrations than BD. However, a subset of individuals with BD may exhibit dysfunctional neurodevelopmental pathways. Abstract: Aberrations in neurodevelopmental trajectories have been implicated in the neurobiology of several mental disorders and evidence indicates a pathophysiological and genetic overlap of schizophrenia and bipolar disorder (BD). In this narrative review, we summarize findings related to developmental and perinatal factors as well as epidemiological, clinical, neuropsychological, brain imaging, postmortem brain and genomic studies that provide evidence for a putative neurodevelopmental pathogenesis and etiology of BD. Overall, aberrations in neurodevelopmental pathways have been more consistently implicated in the pathophysiology of schizophrenia compared to BD. Nevertheless, an accumulating body of evidence indicates that dysfunctional neurodevelopmental pathways may be implicated in the underlying pathophysiology of at least a subset of individuals with BD particularly those with an early age of illness onset and those exhibiting psychotic symptoms. A heuristic neurodevelopmental model for the pathophysiology of BD based on the findings of this review is proposed. Furthermore, we critically discuss clinical and research implications of this model. Finally, further research directions for this emerging field are provided.